Building political capital through corporate social responsibility: A microlevel focus on the role of business leaders - Borges, A.; Ramalho, N. (Social Responsibility Journal, 2023)
There are no management decisions deprived of ethical or political consequences. Political corporate social responsibility (CSR) has been highlighting this assertion but research at the microlevel on this topic is scarce. This study aims to contribute to the microlevel research by proposing a behavioral framework where leaders’ political skills are determinants of engagement in strategic CSR and perceived CSR leverages their ascribed legitimacy to perform a political role outside the boundaries of the organizations. Design/methodology/approach: Building upon political CSR and critical realism theories, this study offers a general review on key political CSR microlevel concepts and examines multiple dimensions of CSR to explain the indirect effect between boards' political skills and political legitimacy. Findings: This research suggests that high politically skilled leaders are associated to more CSR adoption which fosters higher legitimacy to act as political influencers. Among these, CSR activities directed toward community members and employees are seemingly the most successful from a political standpoint. Originality/value: This study proposes a contemporary form of political influence to business leaders that, in contrast with other strategies such as lobbying or financing political campaigns, does not end up damaging corporate image and reputation. Also, this study proposes that not all CSR activities leverage corporate political legitimacy per se, therefore they do need to be differentiated. This study then offers a comprehensive future research agenda, including detailed suggestions for research designs and measurements.